Ranking Executive Actions of Technology Roadmap with the Emphasis on Resources and Technology Acquisition (A Case Study of Two International Roadmaps) - Kiarash Fartash; Mostafa Mohseni Kiasari (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The main objective of this paper is to rank the executive actions of the technology roadmaps with an emphasis on resources and technology acquisition. Methodology: Literature on the role of technology, including approaches, frameworks of roadmap drawing, technology uses, and several primarily up-to-date technology maps, were reviewed. In the next step, two technology roadmaps published by the International Energy Agency were selected to rank the executive actions. These two roadmaps were produced in 2011, with the horizon of 2050. These two roadmaps were studied, and the infrastructure needed to achieve their goals was extracted. Eventually, the battery was selected as the main challenge in the resource layer and technology acquisition for ranking. Findings: Five batteries from the family of ion-lithium batteries (with six technical characteristics) were ranked by TOPSIS and PROMETHEE. For clarity, the six ordinary electric cars on the world market have been compared and ranked. Originality/Value: The results of this research can be used to increase global competitiveness, used by domestic car manufacturers, and as a guideline to determine the priorities of the executive actions that need to be undertaken by Iranian firms.